2014
DOI: 10.1093/carcin/bgu047
|View full text |Cite
|
Sign up to set email alerts
|

Bis-butanediol-mercapturic acid (bis-BDMA) as a urinary biomarker of metabolic activation of butadiene to its ultimate carcinogenic species

Abstract: Human carcinogen 1,3-butadiene (BD) undergoes metabolic activation to 3,4-epoxy-1-butene (EB), hydroxymethylvinyl ketone (HMVK), 3,4-epoxy-1,2-butanediol (EBD) and 1,2,3,4-diepoxybutane (DEB). Among these, DEB is by far the most genotoxic metabolite and is considered the ultimate carcinogenic species of BD. We have shown previously that BD-exposed laboratory mice form 8- to 10-fold more DEB-DNA adducts than rats exposed at the same conditions, which may be responsible for the enhanced sensitivity of mice to BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…22 THBMA concentrations were also determined in the same urine samples using HPLC-ESI − -MS/MS methodology recently developed in our laboratory. 18;33 We found that MHBMA, DHBMA, THBMA, and the metabolic ratio MHBMA/(MHBMA+DHBMA+THBMA) were correlated with BD exposure concentrations. Furthermore, significant associations were also observed between BD urinary mercapturic acids and their corresponding hemoglobin adducts, N , N -(2,3-dihydroxy-1,4-butadiyl)-valine ( pyr -Val) and 2,3,4-trihydroxybutyl-valine (THB-Val).…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…22 THBMA concentrations were also determined in the same urine samples using HPLC-ESI − -MS/MS methodology recently developed in our laboratory. 18;33 We found that MHBMA, DHBMA, THBMA, and the metabolic ratio MHBMA/(MHBMA+DHBMA+THBMA) were correlated with BD exposure concentrations. Furthermore, significant associations were also observed between BD urinary mercapturic acids and their corresponding hemoglobin adducts, N , N -(2,3-dihydroxy-1,4-butadiyl)-valine ( pyr -Val) and 2,3,4-trihydroxybutyl-valine (THB-Val).…”
Section: Introductionmentioning
confidence: 74%
“…Among the three BD-mercapturic acids, the order of urinary concentrations was DHBMA > THBMA > MHBMA, consistent with previous report in smokers. 38 Occupationally exposed workers were exposed to significantly higher concentrations of BD (0.55 ± 0.50 mg/m 3 ) than control workers (0.007 ± 0.005 mg/m 3 ) (Table 2) and hence the concentrations of all three urinary BD-mercapturic acids were increased in occupationally exposed workers as compared to controls (Table 2). …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although the metabolism of MA is not well understood, glutathione-S-transferase (GST) usually plays an important role in detoxification of industrial chemicals to form their corresponding glutathione conjugates, which are further metabolized to N-acetyl cysteine adducts, also named as mercapturic acids (Habig et al, 1974;Hecht et al, 2008). These mercapturic acids have been well studied to serve as biomarkers to assess current exposures for these chemicals in our living environments and/or at workplaces (Alary et al, 1995;Eckert et al, 2013;Huang et al, 2007;Kotapati et al, 2014;Kuiper et al, 2010;Maestri et al, 1997;Perbellini et al, 2002). If MA is also detoxified by GST, the resulting MA glutathione conjugates can be further metabolized to 2-{[2-(acetylamino)-2-carboxyethyl]sulfanyl}butanedioic acid, the mercapturic acid of MA (MAMA) excreted through urine.…”
Section: Introductionmentioning
confidence: 99%